Renewable Energy Consumption, ESG Reporting, and Fixed Asset Turnover: Does it Work in Asia? - Widianingsih, Luky Patricia; Kohardinata, Cliff; Vlaviorine, Emelie (International Journal of Energy Economics and Policy, 2024)
The purpose of this study is to provide empirical evidence on the effect of renewable energy use and ESG reporting on fixed asset turnover of companies in the energy industry and basic materials industry in the Asian region. No one has tried to see the effect of renewable energy consumption and ESG on the company’s efficiency performance through fixed asset optimization, especially in the Asian region which is a strategic region for sustainability goals. The finding is renewable energy does not affect the fixed assets turnover of companies in the energy industry sector and the basic materials industry in Asia. However, ESG reporting represented by ESG score has a significant positive influence on the company’s fixed asset turnover. The company’s overall internal readiness aspect is an important thing that must be considered first so that the implementation of business practices that prioritize natural resource management in achieving operational activity efficiency advantages can achieve its benefits. A higher ESG score is a representation of controlled activity performance management in generating sustainable corporate efficiency through a higher fixed asset turnover ratio, and vice versa.